Effect of A+ (A = Li, Na and K) co-doping on the luminescence enhancement of CaSr2(PO4)2:Dy3+ phosphors for white light-emitting diodes. Issue 17 (1st December 2017) - Dai, Siyi; Zhang, Wentao; Zhou, Dongsheng; Yan, Guilin; Liu, Sutian
Abstract: CaSr2 (PO4 )2 :Dy 3+, A + (A = Li, Na and K) phosphors were prepared through high temperature solid-state reaction. Structures of as-prepared CaSr2 (PO4 )2 :Dy 3+, A + samples agreed well with standard phase of Ca2 Sr(PO4 )2, and the corresponding X-ray diffraction peaks were shifted to smaller 2θ values due to Sr 2+ ions occupying Ca 2+ sites. Effects of Dy 3+ concentration and charge compensator A + on the structure and luminescence properties of CaSr2 (PO4 )2 :Dy 3+, A + phosphors were investigated in detail. Under UV excitation at 353 nm, all CaSr2 (PO4 )2 :Dy 3+, A + samples exhibited two emission peaks at 488 nm and 580 nm, which were due to the 4 F9/2 → 6 H15/2 and 4 F9/2 → 6 H13/2 transitions of Dy 3+ ions, respectively. White light-emitting diode was fabricated by using these white-emitting single-composition CaSr2 (PO4 )2 :Dy 3+, A + phosphors. Luminescence intensity and decay time of CaSr2 (PO4 )2 :Dy 3+, A + phosphors were improved remarkably with the addition of charge compensators, which would promote their applications in white light-emitting diodes with near- ultraviolet chip.